Augmented Reality: Current and New Trends in Education - Kaminska, Dorota; Zwolinski, Grzegorz; Laska-Lesniewicz, Anna; Raposo, Rui; Vairinhos, Mario; Pereira, Elisabeth; Urem, Frane; Ljubic Hinic, Martina; Haamer, Rain Eric; Anbarjafari, Gholamreza (MDPI, 2023)
The educational landscape is an environment prone to change due to the volatile and ever-changing nature of the digital society in which we all live. Although the world moves at different speeds and any generalization is bound to have some exceptions, there is evidence from research conducted in different places and contexts that educational methods are becoming increasingly digitized and driven by technological innovation. Among the technological trends fueled in many cases by the COVID-19 pandemic and the need to stay at home but online, augmented reality solutions received an additional boost as a valid and versatile educational technology worth exploring and eventually integrating into several teaching methods already in use. Although the technology still faces problems related to affordability, accessibility, and the technical skills required of users, some ongoing projects have already provided evidence that using augmented reality solutions as teaching and learning tools can improve teacher and student learning outcomes by increasing engagement and interactivity. The same issues arose when personal computers, tablets, and smartphones were first discussed as valuable tools for education and have now found their way into most classrooms. This paper reviews some of the key concepts related to augmented reality, as well as some current trends, benefits, and concerns related to its integration into educational contexts in areas such as life sciences, engineering, and health. The work conducted and presented in this paper provides an interesting insight into a technology that has given rise to global phenomena such as Pokemon Go, and continues to improve in terms of portability, usability, and overall user experience. Throughout the paper and in the conclusion section, we discuss the relevance of using the best features of augmented reality and how they can contribute to positive educational outcomes.
Keywords: augmented reality; education; EdTech; survey; VIRTUAL-REALITY; MEDICAL-STUDENTS; DESIGN; TOOL; ENVIRONMENTS; SYSTEM; SKILLS; NEEDS; Computer Science; Engineering; Physics